2016
DOI: 10.3168/jds.2015-10258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in situ versus in vitro methods of fiber digestion at 120 and 288 hours to quantify the indigestible neutral detergent fiber fraction of corn silage samples

Abstract: Ruminal digestion of neutral detergent fiber (NDF) is affected in part by the proportion of NDF that is indigestible (iNDF), and the rate at which the potentially digestible NDF (pdNDF) is digested. Indigestible NDF in forages is commonly determined as the NDF residue remaining after long-term in situ or in vitro incubations. Rate of pdNDF digestion can be determined by measuring the degradation of NDF in ruminal in vitro or in situ incubations at multiple time points, and fitting the change in residual pdNDF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 13 publications
1
37
1
6
Order By: Relevance
“…The kd starch (per hour) was calculated from the IVSD data after 7 h of rumen incubation, using a first-order model with a fixed discrete lag time of 0.5 h. A fixed indigestible starch fraction (iStarch) of 0.5% starch was used because the 120-h IVSD values were greater than 98 to 99% starch in all analyzed samples. Thus, the kinetic model (Bender et al, 2016) was…”
Section: Short Communicationmentioning
confidence: 99%
“…The kd starch (per hour) was calculated from the IVSD data after 7 h of rumen incubation, using a first-order model with a fixed discrete lag time of 0.5 h. A fixed indigestible starch fraction (iStarch) of 0.5% starch was used because the 120-h IVSD values were greater than 98 to 99% starch in all analyzed samples. Thus, the kinetic model (Bender et al, 2016) was…”
Section: Short Communicationmentioning
confidence: 99%
“…Neutral detergent fibre (NDF) concentration of forages varies from 30% to 80% of DM (Dry Matter) with a wide variation for its digestibility [1]: from less than 40% for highly lignified mature legumes to greater than 90% for unlignified immature grass [2]. The accurate estimation of the NDF digestibility (NDFD) is important because ruminant nutritionists and forage plant breeders use in vitro measures of NDFD to assess forage quality, predict diet digestibility, and select plant genotypes for breeding [2].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, these contradicting results reflect differences between the tested EOC, used doses (often not economically suitable for commercial livestock), as well as diet/substrate characteristics (Kilic et al, 2011), but may also reflect analytical differences either of the in situ method or the selected NDF analysis. The wide variation in methodologies analysing NDFD is well documented and in several studies differences between the in situ and the in vitro methods were reported (e.g., Spanghero et al, 2003;Bender et al, 2016). It appears that EO and EOC at a specific dose can exert a different effect on digestibility and this effect can be dependent on both fermented substrate and tested plant extract.…”
Section: Introductionmentioning
confidence: 99%